Structural characterization and bioactivity of sulfated Galactan GSSG-2 from Gracilaria salicornia: Antioxidant and anticancer potential - Mythileeswari Lakshmikanthan; Sakthivel Muthu; Peer Mohamed Deen Mohamed; Kathiravan Krishnan; Nagaraj Karuppiah; Ramamoorthy Karuppan; Shenbhagaraman Ramalingam; Anandhi Subramanian; Bharathi Venkatachalam; Gholamreza Abdi (Food Hydrocolloids for Health)
The sulfated galactan GSSG-2, isolated from Gracilaria salicornia, was investigated for its antioxidant and anticancer properties. Polysaccharides derived from marine sources are well-known for their distinctive bioactivities, making them promising candidates for pharmaceutical applications. Purification of GSSG-2 was achieved through a two-step procedure consisting of anion-exchange chromatography utilizing a DEAE-Sepharose column, followed by size-based separation via Sephadex G-100 gel filtration chromatography. Its structural features were characterized using elemental analysis, high-performance gel permeation chromatography (HPGPC), high-performance liquid chromatography (HPLC), Fourier-transform infrared spectroscopy (FT-IR), and nuclear magnetic resonance (NMR) spectroscopy. The antioxidant capacity of GSSG-2 was measured at concentrations from 25 to 150 µg/mL using assays such as DPPH radical scavenging, inhibition of superoxide anions, ferric reducing antioxidant power (FRAP), and total reducing power. In all assays, l-ascorbic acid served as the reference standard. Cytotoxic effects and induction of apoptosis in A549 human lung carcinoma cells were assessed employing MTT assays and acridine orange/ethidium bromide (AO/EtBr) fluorescence staining. GSSG-2 demonstrated a molecular weight of 70.61 kDa, with galactose identified as the dominant monosaccharide unit (328.92 mg/g). Its antioxidant activity showed a dose-dependent increase, ranging from 19.84% to 88.59%. The IC₅₀ value determined by the MTT assay was 100 µg/mL, and cell viability dropped dramatically to 16.0% at 250 µg/mL. Results from AO/EtBr staining further corroborated the time-dependent enhancement of apoptotic cell death. The strong antioxidant and anticancer effects of GSSG-2 are attributed to its structural components, notably the esterified sulfate moieties and β-(1→3)-linked d-galactopyranose units. These results underscore the potential of this compound as a therapeutic agent targeting oxidative stress and cancer.